(untitled) (Research, Society and Development, 2024)
Introduction: Autism Spectrum Disorder (ASD) is a neurological condition that presents with symptoms that vary in intensity and manifestation. It affects approximately 2 in every 1,000 births and is four times more prevalent in male children compared to female children. It is a condition that is observed in several parts of the world. Objective: To develop a descriptive analysis of the performance of the multidisciplinary health team on Autism Spectrum Disorders and their impacts on the daily lives of those living on the spectrum. Methodology: This is a descriptive bibliographic review with a qualitative approach, based on scientific studies on the interdisciplinary approach in assisting autistic children. It was carried out through a search in the LILACS, SCIELO, BVS Literature databases and on the Ministry of Health’s reference website. The selected articles met the following inclusion criteria: those published from 2014 to 2023, complete in Portuguese. Results and Discussion: Based on the analysis of scientific studies, it was possible to observe that the studies showed that autism is a condition that begins early, where difficulties usually compromise the child’s development throughout his or her life. In this sense, there is a variety related to the intensity and form of expression of the symptoms, in the areas that define its diagnosis. Final Considerations: It is concluded that, as it is a heterogeneous disease, for the ideal therapeutic direction with a multidisciplinary team that will promote greater stimulation for the affected child, the diagnosis should be made as early as possible.